Wyprawa Cyrusa i odwrót Dziesięciu Tysięcy w przekazie Diodora (14.19–31; 37.1–4): Przekład i komentarz - Głogowski, Piotr (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2018)
The author presents the first Polish translation of the section of the work by Diodorus Siculus devoted to the expedition of Cyrus the Younger and the Retreat of the Ten Thousand (Diod. 14.19–31; 37.1–4). The translation is supplemented by the commentary, which focuses mainly on the problem of the sources exploited by the direct source of Diodorus in this part of his work – Ephorus of Cyme. Therefore, the basic aim of the commentary is to display the similarities and differences between the narrative of Diodorus and the Anabasis of Xenophon and other sources, e.g. Persica by Ctesias of Cnidus.